Effects of Single Nucleotide Polymorphisms in the SLC27A3 Gene on the Nutritional Value of Sheep Milk - Ewa Pecka-Kiełb; Inga Kowalewska-Łuczak; Ewa Czerniawska-Piątkowska; Anna E. Zielak-Steciwko (Animals, 2020)
The current research was undertaken to use the genetic potential of animals to obtain high-quality dairy products. Single nucleotide polymorphisms (SNPs) in SLC27A3 gene were identified in Zošľachtená valaška sheep using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Correlations between genotypes and milk composition and nutritional value were analysed This study showed that milk from sheep with TT genotype in the SNP4 locus was characterised by higher (p < 0.01) fat and dry matter content and lower lactose concentration, compared to sheep with AA and TA genotypes, respectively. Moreover, it was found that animals with GG genotype in SNP1 produced milk with higher C18:1n9c, C18:1n7t, CLA, and other unsaturated fatty acids (UFAs) content than sheep with TT. Additionally, milk from animals with CC at the SNP3 locus had significantly higher (p < 0.01) levels of UFAs than milk from sheep with other genotypes in the SNP3. In summary, it may be concluded that milk from animals with TT genotype of SNP4 is characterised by higher fat and dry matter content. Whereas, milk from sheep with GG in SNP1 and with CC in SNP3 is characterised by higher content of UFAs, which increases milk value as material for functional food production.